Peptic Ulcer Disease and Helicobacter pylori Infection in Different Siberian Ethnicities. Issue 1 (6th June 2016) - Tsukanov, Vladislav V.; Kasparov, Edward V.; Tonkikh, Julia L.; Shtygasheva, Olga V.; Butorin, Nikolay N.; Amelchugova, Olga S.; Vasyutin, Alexander V.; Bronnikova, Elena P.; Fassan, Matteo; Rugge, Massimo
Abstract: Background: The high prevalence of Helicobacter pylori ( H. pylori ) infection in eastern Siberia is consistently established. In the same geographic area, however, fragmentary information is available on the epidemiology of the peptic ulcer disease (PUD). Aim: To assess the prevalence of H. pylori infection (including CagA status ) and PUD in different eastern Siberian ethnicities. Patients and Methods: An endoscopy population of 3149 eastern Siberian dyspeptic patients was considered [1727 Europoids and 1422 Mongoloids (Evenks = 792; Khakases = 630)]. H. pylori status was assessed by urease test and/or serum anti‐ H. pylori IgG and/or histology. CagA status was serologically assessed (anti‐CagA antibodies). Results: All the Siberian ethnicities featured high rates of H. pylori infection (Europoids = 87.1%, Evenks = 88.6%, Khakases = 85.4%). Among the 1504 H. pylori ‐positive Europoids, the prevalence of CagA‐positive status (68.7%) was significantly higher than that featured by the 1240 H. pylori ‐positive Mongoloid ethnicities (46.9%; p < .001 for both comparisons). Peptic ulcer disease significantly prevailed among Europoids (prevalence among Europoid Evenks and Khakases: 8.9% and 8.3%, respectively; prevalence among Mongoloid Evenks and Khakases = 1.0% and 4.4%, respectively). Conclusions: eastern Siberian populations feature consistent high rates of H. pylori infection, but different prevalence of peptic ulcer disease. In particular, Europoids featured a prevalence of both CagA‐positive status and peptic ulcer disease significantly higher than that of the Mongoloid ethnicities. These results suggest that both environmental factors (coexisting with the H. pylori infection) and host‐related variables modulate the clinicopathological expression of the H. pylori ‐associated gastric diseases.